PROYECTO DE TOMÁS MONTALVO PARA UN PUENTE DE ALJUCER (1752) - de la Peña Velasco, Concepción (Imafronte, 1995)
The aim of this paper is to make known a project by Tomás Montalvo, stressing that he is one of the most important artists in the Murcia of the second third of the 18th century, although still practically unknown.